A Modern Treatment of the Ricardian Economy: I. The Pricing of Goods and of Labor and Land Services - Samuelson, Paul A. (Quarterly Journal of Economics, 1959)
Introduction, 1. — In the beginning, 3. — The expanding universe, 5. — Scarcity of land and positive rent, 7. — Residual rent to homogeneous land, 9. — A numerical example, 10. — The case of many goods and homogeneous land, 12. — The Leontief-Ricardo tableau, 15. — Non-substitutability even where substitutability is possible, 16. — Summary and Conclusion, 18. — Appendix: Theory of differential rent, 20.